Examining STEM Students' Computational Thinking Skills through Interactive Practicum Utilizing Technology - Verawati, Ni Nyoman Sri Putu; Rijal, Khaerul; Grendis, Nuraqilla Waidha B (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
This research study explores and compares the computational thinking skills demonstrated by STEM students during interactive practicums involving both virtual laboratories and physical laboratories. The objectives of the study are to assess the performance of computational thinking skills in each practicum setting and to determine any differences between the two environments. An experimental approach was adopted, and 106 first-year STEM students from a distinguished private university in Indonesia participated in the study. The students were divided into two groups, one using virtual labs and the other using physical labs. The study employed a portfolio instrument to assess various aspects of computational thinking, including problem reformulation, recursion, problem decomposition, abstraction, and systematic testing. The findings show that both groups of students achieved